Final answer:
The system is solved by substituting the expression for y from the first equation into the second. Solving for x and then y, the solution is found to be x=1 and y=7.
Step-by-step explanation:
To solve the system by substitution, you can take the expression for y from the first equation and substitute it into the second equation. The first equation y=7x allows us to understand that wherever we see a y in the second equation, we can replace it with 7x. So the second equation x-7y=-48 becomes x-7(7x)=-48, which simplifies to x-49x=-48 or -48x=-48. Solving for x we get x=1. Plugging this back into the first equation to find y, we get y=7(1)=7. Hence, the solution to the system is x=1 and y=7.